Moment of truth : redefining the CEO's brand management agenda - Bauer, Andreas (Libros electrónicos en Ebscohost, 2006)
The authors argue that a paradigm shift is needed with regard to brand management. Many companies and organizations have seen brand management as a narrow marketing activity and this has resulted in weak brands. By contrast they argue for a holistic approach to branding with the brand at the centre of a value-based approach and the focal point of business strategy. They show how to develop brand strategy and brand engagement as part of a brand-centric organization.